Long-term follow-up of metabolic activity in human alveolar echinococcosis using FDG-PET - Reuter, S.; Grüner, B.; Buck, A. K.; Blumstein, N.; Kern, P.; Reske, S. N. (Nuklearmedizin - NuclearMedicine, 2008)
Aim: [18F]fluoro-deoxyglucose positron-emission-tomography (FDG-PET) detects metabolic activity in alveolar echinococcosis (AE). The slow changes in metabolic and morphological characteristics require long-term follow-up of patients. This is the first study to evaluate metabolic activity over may years, hereby assessing the utility of FDGPET for the evaluation of disease progression and response to treatment. Patients, methods: 15 patients received a follow-up FDG-PET combined with computed tomography (integrated PET/CT) with a median of 6.5 years after the first PET in 1999. Number and location of enhanced metabolic activity in the area of AE lesions was determined. Quantification of intensity of metabolic activity was assessed by calculation of mean standardized uptake values. Results: AE lesions in 11/15 patients had been metabolically inactive initially, but only two showed permanent inactivity over the course of 81 months. Interestingly, in two patients metabolic activity was newly detected after 80 and 82 months. Benzimidazole treatment was intermittently discontinued in seven cases. Persisting activity at FDG-PET demanded continued benzimidazole treatment in four patients. Neither treatment duration, lesional size, calcifications nor regressive changes correlated with metabolic activity. Conclusion: Treatment responses are heterogeneous and vary from progressive disease despite treatment to long-term inactive disease with discontinued treatment. Lack of metabolic activity indicates suppressed parasite activity and is not equivalent to parasite death. However, metabolic activity may remain suppressed for years, allowing for temporary treatment discontinuation. Relapses are reliably detected with PET and restarting benzimidazole treatment prevents parasite expansion.
Keywords: Echinococcus multilocularis; treatment; imaging; parasitostatic; disease activity